2020
DOI: 10.1891/vv-d-19-00042
|View full text |Cite
|
Sign up to set email alerts
|

Sex Trafficking Knowledge and Training: Implications From Environmental Scanning in the American Midwest

Abstract: Large gaps exist in our knowledge about the effectiveness of sex trafficking training. This study surveyed knowledge and training regarding sex trafficking among service providers (N = 66; i.e., social workers, law enforcement offers, and medical providers) in one Midwestern state. The study aimed to: (a) determine the goodness-of-fit between respondents' agency criteria for victim identification and established trafficking definitions, (b) assess training desired and received, and (c) examine group difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…32 Hence, anti-human trafficking service providers perceive a need for developing basic services related to accessibility and delivery of services and more training on human trafficking and the intersections of human trafficking with other phenomena such as domestic and sexual violence, supporting prior research. 25,26 We also identified needs related to housing and shelter, which supports previous research. 19,25,32,34 A needs assessment in Virginia showed emergency housing as one of the most needed services.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…32 Hence, anti-human trafficking service providers perceive a need for developing basic services related to accessibility and delivery of services and more training on human trafficking and the intersections of human trafficking with other phenomena such as domestic and sexual violence, supporting prior research. 25,26 We also identified needs related to housing and shelter, which supports previous research. 19,25,32,34 A needs assessment in Virginia showed emergency housing as one of the most needed services.…”
Section: Discussionsupporting
confidence: 84%
“…Prior research found human trafficking training in Missouri to be sufficient but lacking in areas such as coordinated case management and trauma-informed identification and intervention. 26 Although most service providers reported having received basic training in human trafficking, they wanted to see more advanced training in best practices, information on key identifiers of human trafficking, case coordination and multidisciplinary team coordination, and trauma-informed care. 26 The findings of our study support previous research showing that training, particularly multidisciplinary training, is a critical need.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations